Importance of Financial Inclusion – A Social Responsibility of Government of Madhya Pradesh - Dr. Meghna Jain (Journal of Social Responsibility, Tourism and Hospitality, 2022)
The term financial inclusion is made up of two words; financial which means anything related to finance and inclusion and it is related to practices which provide equal access towards resources and opportunities to those people who do not get enough opportunities and remain excluded. Financial inclusion is a social responsibility of the government as they need to help those people who are away from the banking facilities. Therefore, financial inclusion means providing equal access to the entire financial product and services to those people who are excluded from such services. Financial Products and Services include banking, insurance, investment, and a lot more. Financial inclusion play an important role in inclusive development and growth of the economy. In India, the central government, state government and RBI have been continuously coming up with new policies and schemes to improve the status of financial inclusion. There are different measures which have been initiated by government which includes Pradhan Mantri Jan Dhan Yojana (PMJDY) and many such others which aim to provide financial strength to the individuals who are not getting much opportunities for their development and growth. This study aimed to understand current status of financial inclusion and also to evaluate various schemes which have been initiated by the government towards the goal of financial inclusion and the study area is Madhya Pradesh. This study is mainly based on secondary data collection and a simple percentage method is used to analyze the data. On the basis of analysis, it is concluded that the nature of financial inclusion can be said to be progressive in nature, but the involvement of private sector banks is still low as compared to public sector banks and regional rural banks.